2013
DOI: 10.3928/00989134-20130313-03
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effect of Companion Robots on Emotional Expression in Older Adults with Dementia: A Pilot Randomized Controlled Trial

Abstract: This pilot study aimed to compare the effect of companion robots (PARO) to participation in an interactive reading group on emotions in people living with moderate to severe dementia in a residential care setting. A randomized crossover design, with PARO and reading control groups, was used. Eighteen residents with mid- to late-stage dementia from one aged care facility in Queensland, Australia, were recruited. Participants were assessed three times using the Quality of Life in Alzheimer's Disease, Rating Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
284
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(292 citation statements)
references
References 26 publications
(24 reference statements)
5
284
0
3
Order By: Relevance
“…One pilot study on Paro assessed wandering, which showed an increased level in the intervention group. 32 The preliminary results of an ethnographic study assessed one severely agitated patient interacting with Paro over the course of 6 months, and found that Paro stimulated emotions and facilitated open communication. 29 Our study measured agitation and found a significant decrease at follow-up according to BARS in the intervention group compared with a slight increase in the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One pilot study on Paro assessed wandering, which showed an increased level in the intervention group. 32 The preliminary results of an ethnographic study assessed one severely agitated patient interacting with Paro over the course of 6 months, and found that Paro stimulated emotions and facilitated open communication. 29 Our study measured agitation and found a significant decrease at follow-up according to BARS in the intervention group compared with a slight increase in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…31 Another cross-over study showed increased pleasure scores and less anxiety in an intervention group with Paro, but there was no effect on depression compared with a reading group as control. 32 The most recent RCT on Paro described effects such as frequent talking, positive expressions, and laughing from individual interaction with Paro compared with interaction with a stuffed toy. 33 Reviews on intervention studies using SARs emphasize weak methodological quality, small samples, short durations, lack of control group, and follow-up measures.…”
mentioning
confidence: 98%
“…20 Cf. by way of example the study currently being conducted by Moyle et al [94]. In a pilot randomized controlled trial, Moyle and her team have already established the positive effect of PARO on the quality of life of nursing home residents with dementia.…”
Section: Sgb XI Zur Qualifikation Und Zu Den Aufgaben Von Zustzlichenmentioning
confidence: 96%
“…More than a third of people with dementia have reported loneliness [2]. Robots have the potential to combat the devastating impact of loneliness in people with dementia by improving, mood, quality of life [3] and reduce social isolation by facilitating people with dementia (PWD) to maintain social contacts. However companion robots designed for PWD need to be customised to meet individual needs if they are to be perceived as useful and acceptable.…”
Section: The Randd or Application Ideamentioning
confidence: 99%